Interaction between Eutypa lata and Trichoderma harzianum - S. John (Phytopathologia Mediterranea, 2004)
Metabolites produced by three strains of Trichoderma harzianum reduced growth of Eutypa lata in vitro. Volatile metabolites produced by T. harzianum were fungistatic towards both isolates of E. lata tested. Growth of some isolates of E. lata was inhibited completely by non-volatile metabolites. Infection by E. lata was reduced in autoclaved grapevine cane segments co-inoculated with spores of T. harzianum and E. lata. Scanning electron microscopic examination of gamma-irradiated cane segments and living cuttings inoculated with T. harzianum and E. lata suggested that antagonism in grapevine wood was mainly by antibiosis. Both the pathogen and the antagonist grew in the xylem vessels and pith parenchyma cells of the wood.